A Single-Center Treatment Experience of Gamma Knife Radiosurgery for Optic Pathway Glioma. (9th August 2022) - Ge, Youlin; Zhang, Zhiyuan; Li, Yanhe; Lin, Yiguang; Zong, Yongqing; Liu, Dong
Abstract : Objectives . To determine the independent prognostic factors that will influence the local tumor control/visual acuity (VA) preservation of optic pathway glioma (OPG) after Gamma Knife radiosurgery (GKS) and to optimize the treatment strategy. Methods . A cohort of 52 consecutive OPG patients who underwent GKS in our center between August 1997 and September 2020 was studied retrospectively. Risk factors such as age at GKS, gender, tumor subtype, tumor site, tumor volume, intratumoral cyst formation, and marginal dose were selected for the univariate and multivariate analysis. COX proportional hazard models were built to determine the independent prognostic factors of local tumor control/VA preservation, and the Kaplan-Meier (K-M) curves were plotted to compare the survival rate among subgroups. Results . 52 OPG patients were included in this study, with a median age of 13.8 years (2-53 years); female outnumbered male at a ratio of 30 : 22; 7 patients (13.5%) had a history of surgical resection; 14 patients (26.9%) were categorized as neurofibromatosis type I (NFI) associated OPG and the rest as sporadic OPG; there were 6 patients (11.5%) with tumors located at hypothalamus/optic chiasm and the rest located in the orbit; the mean tumor volume was 4.36 ml (0.25-11.4 ml); 49 patients (94.2%) presented with VA impairment before GKS; 28 patients (53.8%) underwent single fraction GKS, and the rest underwent fractionated GKS (2-4 fractions); the mean marginal dose (represented with biologically effective dose, BED) was 66.6 Gy (13.3-126.0 Gy); the median follow-up time was 39 months (6-147 months); 11 patients were observed with tumor relapse, 33 with stable disease, and 8 with tumor regression; tumor relapse time varied from 30 to 76 months (mean 54 months); the 1-, 3-, and 5-year progression-free survival (PFS) rates were 100%, 92%, and 78%, respectively; 30 patients were included in the visual analysis; 7 patients were observed with VA deterioration, 19 with stable VA, and 4 with VA improvement; the 1-, 3-, and 5-year VA preservation rates were 92%, 84%, and 77%, respectively. COX proportional hazard risk models showed that intratumoral cyst formation and marginal dose were the only two independent prognostic factors of local tumor control/VA preservation; fractionated GKS provided a higher VA preservation rate than single fraction GKS. Four patients were observed with conjunctive edema/conjunctive hyperemia in 1-4 weeks after GKS. Conclusions . GKS is a safe and effective treatment for OPG either as initial treatment or as salvage treatment after surgical resection, it provides good local tumor control and VA preservation, and fractionated GKS could be a preference for OPG patients with baseline VA ≥ 0.2 .